Multicentric Retrospective Evaluation of Five Classic Infantile Pompe Disease Subjects Under Enzyme Replacement Therapy With Early Infratentorial Involvement - Paoletti, Matteo; Pichiecchio, Anna; Colafati, Giovanna Stefania; Conte, Giorgio; Deodato, Federica; Gasperini, Serena; Menni, Francesca; Furlan, Francesca; Rubert, Laura; Triulzi, Fabio Maria; Cinnante, Claudia (Frontiers in Neurology, 2020)
White matter (WM) abnormalities and ventricular enlargement in brain MRI are well-known features in Infantile Onset Pompe Disease (IOPD) in the era of enzyme replacement therapy (ERT). In this multicentric observational retrospective study, we report a small cohort of IOPD subjects under ERT treatment (n = 5, median age at MRI = 7.4 years, median period of treatment = 85 months) that showed the classic features of extensive supratentorial white matter (WM) abnormalities but also unusual findings as early infratentorial WM abnormalities and late supratentorial U-fibres involvement. Given the recent implementation of ERT and the rarity of the disease, a complete spectrum of presentation and understanding of progressive pathology in the brain of IOPD subjects in treatment remains underacknowledged. The availability of long-term follow-up of IOPD subjects under ERT treatment allows a better insight into the evolution of brain abnormalities in such disease.